HUBUNGAN MINAT BACA DENGAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV SEKOLAH DASAR GUGUS 1 KECAMATAN TAMPAN - Baiduri, Intan; Kurniaman, Otang; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study to determine whether there is a significant relationship between students read the IV gradation SD gugus 1 Kecamatan Tampan learning Indonesia. This research is a kind of quantitative correlation. Subjects in this study were students in the IV gradation Primary School gugus 1 Kecamatan Tampan with a sampel was of 91 students. Sampling was done randomly with a percentage of 20%. Instruments in this study questionnaire about reading and clay Indonesia. Based on the analysis, There are 13 students interest in reading the high category with a percentage of 14.29%, 67 students do categorized by the percentage of 73.62%, and 11 students lower category with the percentage of 12.09%. While the results of the data analysis of student learning results contained 12 high category with a percentage of 13.00%, 74 students do categorized by percentage of 81.30% and 7 students lower category with a percentage of 7.69%. Correlation coefficient values obtained in 0,195, with a significant level of 3,803%, there is no significant relationship between interest in reading by learning results. The relationship between reading interest of students learning results from all IV categories of primary school gugus 1 Kecamatan Tampan were very low.Key Words: Relationship, learning results, reading interest